Validação de método espectrofotométrico para determinação de nitrito em patê de presunto - Patricia Barros Reis (2006)
The validation of an essay method consists of applying the performance characteristics forseen toevaluate the efficiency of routine analysis in laboratory. In this work, the spectrophotometric method wasvalidated as a method to detect and quantify nitrite using as source ham paté. In the methodology used, itwas defined the wave of lenth of 540 nm and the reading of samples between 40 to 70 minutes afteraddition of color reagents. According to the results obtained, the method has linearity in the studied zone(0,125 to 3 mg/mL), matrix effect was not observed, there wasnt any interference of ascorbic acid andthere was interference of sodium eritorbate in concentrations over 2,5 mg/100g. The detection limit wasdefined in 12,5 mg of nitrite/Kg of paté and the quantification limit in 25 mg of nitrite/Kg of paté. Themethod had repeatebility and reproductibility. The accuracy was evaluated through recovery values thatvary from 84 to 110%. In robustness, it was observed that the variations applied to the extractingprocedure depended on the concentration of nitrite in the paté sample